2012
DOI: 10.1111/j.1365-2702.2011.03951.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The impact of nurse short message services and telephone follow‐ups on diabetic adherence: which one is more effective?

Abstract: Both of follow-up intervention uses in this study can decrease HbA1c levels and escalate adherence to diabetes control recommendations in people with type 2 diabetes for three months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 36 publications
5
138
0
5
Order By: Relevance
“…Piette et al kontrol grubuna göre 12 ay telefonla takip edilen ve sesli mesajla izlenen 124 diyabetli bireyin AKŞ düzeylerinin anlamlı ölçüde azaldığını (41 mg/dl) bildirmişlerdir (28). Kim & Jeong telefonla takip ettikleri ve sesli mesajla 3 ay izledikleri diyabetli bireylerin kontrol grubuna göre AKŞ ve TKŞ düzeylerinde azalma olmakla birlikte, aralarında istatistiksel olarak anlamlı bir fark olmadığını Tab lo 3: Araştırma gruplarına göre ÇBDÖ'nin alt boyutlarının önceki ve 12 hafta sonraki puanlarının dağılımı (n=120) (12,13,27,28,32,33,34,35,36,37), bulgumuz önceki çalışma sonuçlarını doğrulamaktadır. Bununla birlikte NICHE çalışmasında 12 haftalık izlem sonunda gruplar arasında HbA1c düzeylerin-de anlamlı bir fark olmadığını bildirilmiştir (38).…”
Section: Discussionunclassified
“…Piette et al kontrol grubuna göre 12 ay telefonla takip edilen ve sesli mesajla izlenen 124 diyabetli bireyin AKŞ düzeylerinin anlamlı ölçüde azaldığını (41 mg/dl) bildirmişlerdir (28). Kim & Jeong telefonla takip ettikleri ve sesli mesajla 3 ay izledikleri diyabetli bireylerin kontrol grubuna göre AKŞ ve TKŞ düzeylerinde azalma olmakla birlikte, aralarında istatistiksel olarak anlamlı bir fark olmadığını Tab lo 3: Araştırma gruplarına göre ÇBDÖ'nin alt boyutlarının önceki ve 12 hafta sonraki puanlarının dağılımı (n=120) (12,13,27,28,32,33,34,35,36,37), bulgumuz önceki çalışma sonuçlarını doğrulamaktadır. Bununla birlikte NICHE çalışmasında 12 haftalık izlem sonunda gruplar arasında HbA1c düzeylerin-de anlamlı bir fark olmadığını bildirilmiştir (38).…”
Section: Discussionunclassified
“…The minimum difference reported at the end of the study period in the intervention group was -0.1 (6.4% pretest to 6.3% at 3 months) while the maximum difference was -2.4 (9.8% pretest to 7.4% at 3 months). Ten studies showed lower HbA1c levels among participants in the intervention group at the end of the intervention, although only seven 17,19,20,25,27,28,30 reported significant reduction in HbA1c levels (p < 0.05). Meta-analysis suggests that during an average followup of 6.3 years, an overall net effect of HbA1c reduction of the 12 studies in intervention groups was 0.39% (95%CI: -0.067, -0.72, p=0.018) after taking off the reduction in control groups.…”
Section: Effects Of Interventionmentioning
confidence: 98%
“…[14][15][16][17] Active participation in lifestyle management and the feedback regarding blood glucose levels were mainly discussed in studies of CPBMI in diabetes patients and healthcare providers. [18][19][20][21][22][23][24] Notably, many articles reported the use of CPBMI in enabling lifestyle modification in the treatment of all three diseases, but they described the use of different services in accordance with the characteristics of each disease. Articles that examined the use of CPBMI by diabetes patients and healthcare providers reported that programs with IT infrastructure showed increased effectiveness of management, even with a minimal number of hospital visits.…”
Section: Current Clinical Usementioning
confidence: 99%